Institutional aspects of the regulation of the activity of the raw-mineral complex of Russia - S. V. Lisov (Известия высших учебных заведений: Геология и разведка)
The system defects of the federal legislation on subsoil are shown. They include such problems as: base terms meanings; formation of the strategies and programs in subsoil use sector; regulation of the property relations and order of licensing. More thorough account of the federal legislation about strategic planning in subsoil use sector is important. The present institutional norms don’t take into account the demands of the economic diversification, the increase of the products of mineral processing. That’s why the subsoil use sector is recommended to be applied with federal legislation concepts of industrial policy, which main task is to declare the transmission to the innovational type of the economy.